Density, planning, and the emergent landscapes of purpose-built student accommodation in England - Livingstone, Nicola; Fiorentino, Stefania; Short, Michael (Frontiers in Sustainable Cities, 2023)
This mini review explores perspectives on density and discretionary planning policy in relation to the emergent landscapes of purpose-built student accommodation (PBSA) across selected English university cities. It examines the nexus between density in planning policies and transformations in student accommodation, presenting a research gap requiring further investigation. Our research builds upon limited literature on UK PBSA within which there has been inadequate interrogation of policy impacts on the substantial growth of this now mature market sector. By better understanding the relations between national planning policies and their local interpretations regarding PBSA, we can move toward improving understandings for urban futures. The intersectionality between the evolution of the PBSA sector and the planning system are currently underexplored. The paper highlights the proliferation, densification, and concentration patterns of PBSAs and their connections to the surrounding planning system. The emergence of privately developed PBSA in the UK is typically characterized by medium to high rise, and medium to high density development. Higher density PBSA has created a dynamic spectrum of impacts reflecting subjective perceptions of their emergence in university cities. Our mini review illustrates the growth trajectory and direction of the PBSA sector. We conclude with a reflection on the discretionary nature of planning policies for density that often create regulatory loopholes allowing PBSA to thrive as a niche real estate asset class but not necessarily as a local and social collective asset.